A mixed pressing method of printed circuit board and printed circuit board

CN122952512APending Publication Date: 2026-10-20VICTORY GIANT TECH HUIZHOU CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610877798.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-17
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

通过采用无玻纤碳氢树脂涂树脂铜箔替代传统的含Q布PP材料,本方案首先解决了盲孔加工中Q布无法气化的根本性问题

Benefits of technology

1.从根本上解决了M9等级高速印制线路板盲孔加工中Q布无法激光气化的技术瓶颈。采用无玻纤碳氢树脂涂树脂铜箔替代传统的含Q布PP材料,碳氢树脂为有机高分子材料,在激光高能作用下可有效裂解气化,无需处理玻纤残留。该方案绕开了Q布纯二氧化硅成分对激光加工的根本性障碍,为224G高速印制线路板的产品开发打通了材料技术路线。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
Patent Text Reader

Abstract

This invention discloses a method for mixing and pressing printed circuit boards (PCBs) and the PCB itself. The mixing and pressing method includes: providing a blind via layer material, which is a glass fiber-free hydrocarbon resin-coated copper foil with a rough surface structure having interconnected micropores; alternately stacking the blind via layer material and the buried via layer material to form a stack to be pressed; heating and pressurizing under vacuum conditions at a first temperature and a first pressure to expel gas from the interconnected micropores of the copper foil; and gradually increasing the temperature and pressure to the curing temperature and curing pressure while maintaining the vacuum conditions, causing the hydrocarbon resin to flow, fill the interlayer gaps, and cure and bond. This solution utilizes the microporous structure of the RCC copper foil as an in-situ venting channel, combined with vacuum low-temperature venting and a gradual temperature-increasing curing process, effectively solving the problems of Q-cloth laser vaporization failure and air bubbles in the mixing and pressing of heterogeneous materials in M9-grade high-speed PCBs. A PCB manufactured by the above method is also provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of printed circuit board manufacturing technology, specifically to a method for mixing and pressing multilayer printed circuit boards for high-speed signal transmission and the printed circuit boards manufactured by this method. Background Technology

[0002] With the iterative development of communication technology, signal transmission rates are constantly increasing. In high-speed signal transmission scenarios with speeds of 224G and above, the dielectric loss and signal integrity of printed circuit boards (PCBs) have become key factors restricting system performance. To address this, the industry has developed high-speed materials of grades M8 and M9, which reduce energy attenuation during signal transmission by lowering the dielectric loss factor (DF value) of the substrate.

[0003] Currently, mass-produced high-speed printed circuit boards (PCBs) on the market mainly use materials of M8 grade and below, with their dielectric constant (DF) values ​​typically defined as above 0.001. Among M8 and below grade materials, the fiberglass cloth in the prepreg (PP) uses Low DK (low dielectric constant) fiberglass cloth, with a silica content of approximately 50%-60%. The dielectric properties of the material can be controlled by adding fillers. During the laser drilling process of PCBs, this Low DK fiberglass cloth can be vaporized and removed under laser irradiation, thus successfully completing the formation of blind vias.

[0004] However, when the material grade was upgraded to M9 to meet the requirements of 224G signal transmission, the industry began to use Q-cloth (Quartz cloth, quartz fiber cloth) as a reinforcing material. The main component of Q-cloth is pure silica, and its chemical composition is consistent with that of glass. Pure silica has a high melting point and strong chemical stability. Under the laser wavelength and energy density conditions used in conventional laser drilling of printed circuit boards, Q-cloth is difficult to vaporize effectively, resulting in serious glass fiber residue after drilling and causing unqualified blind via quality. Even with attempts to adjust laser parameters or use multiple drilling processes, it is still difficult to completely remove Q-cloth residue, and technological breakthroughs have encountered a bottleneck.

[0005] In traditional high-speed printed circuit board (PCB) lamination processes, polypropylene (PP) (prepreg) is used as the interlayer adhesive in the laminated structure. PP consists of fiberglass cloth and impregnated resin. During lamination, the resin in the PP melts and flows under temperature and pressure, filling the gaps in the circuit pattern and achieving interlayer bonding. However, when using thin PP or when two PP sheets are stacked, if the residual copper content of the circuit pattern is high or the copper thickness is large, the resin's filling capacity will be significantly insufficient, easily resulting in voids caused by inadequate filling in the groove areas of the copper foil outline. Furthermore, since high-speed materials generally use open-fiber cloth, both sides of the fiberglass cloth are coated with resin. During lamination to fill the gaps, mainly the resin on the side closer to the substrate participates in the flow and filling, while the resin on the side farther from the substrate is difficult to effectively participate in filling. This results in low actual resin utilization, further exacerbating the problem of insufficient filling.

[0006] When the technology advanced to M9-grade Q-cloth PP, the aforementioned problems became even more severe: on the one hand, the pure silica composition of Q-cloth made laser drilling impossible; on the other hand, Q-cloth PP also suffered from insufficient resin filling capacity during the lamination process. These combined technical obstacles posed a significant challenge to the mass production of 224G high-speed printed circuit boards using the M9 Q-cloth technology. Summary of the Invention

[0007] The first aspect of this invention provides a method for bonding blind via layer material and buried via layer material into a printed circuit board, comprising the following steps: providing a blind via layer material, wherein the blind via layer material is a glass fiber-free hydrocarbon resin-coated copper foil, the copper foil having a rough surface structure with interconnected micropores; alternately stacking the blind via layer material and the buried via layer material to form a stack to be pressed; heating and pressurizing the stack to be pressed under vacuum conditions at a first temperature and a first pressure to expel gas from the interconnected micropores of the copper foil; and gradually increasing the temperature and pressure to a curing temperature and a curing pressure while maintaining vacuum conditions, causing the hydrocarbon resin to flow, fill the interlayer gaps, and cure and bond. By using glass fiber-free hydrocarbon resin-coated copper foil instead of traditional Q-cloth-containing PP material, this solution first solves the fundamental problem of the inability of Q-cloth to vaporize during blind via processing. Secondly, this solution utilizes the interconnected micropores and rough surface structure of the RCC copper foil itself as an in-situ venting channel: Under low-temperature and low-pressure vacuum conditions, the hydrocarbon resin has not yet softened and flowed, and the micropores of the copper foil remain open. At this time, vacuuming can fully remove air, moisture, and low-molecular-weight volatiles from the stack before the resin flow window closes. After venting is completed, the temperature and pressure are gradually increased while maintaining vacuum. The hydrocarbon resin gradually melts and flows to fill the interlayer gaps, eventually reaching the curing temperature to complete curing and bonding.

[0008] Furthermore, the buried via layer material is a resin substrate with a glass transition temperature of not less than 200°C. Limiting the TG value of the buried via layer material to above 200°C ensures that the circuit board does not soften or deform during subsequent high-temperature processes such as lead-free soldering, while also providing a clear benchmark for setting the curing temperature.

[0009] Furthermore, the buried via layer material is a BT resin-based copper clad laminate or a BT resin-based prepreg. BT resin has excellent heat resistance and a low coefficient of thermal expansion, making it a mature material choice for high-reliability applications at the substrate level.

[0010] Furthermore, the stepwise increase of temperature and pressure to the curing temperature and pressure includes: first, gradually increasing the temperature and pressure from the first temperature and pressure to a second temperature and pressure, and maintaining this temperature and pressure for a predetermined time to allow the hydrocarbon resin to fully flow and fill the interlayer gaps, before further increasing the temperature and pressure to the curing temperature and pressure. This two-stage heating scheme provides an independent flow window for the hydrocarbon resin, making it particularly suitable for circuit patterns with high residual copper content or deep and narrow gaps.

[0011] Furthermore, when the buried via layer material is a resin substrate with a glass transition temperature of not less than 200°C, the curing temperature reaches or exceeds the glass transition temperature of the buried via layer material. A curing temperature reaching or exceeding the TG value ensures that the buried via layer resin is sufficiently softened and flowable, achieving molecular-level diffusion bonding with the hydrocarbon resin at the interface.

[0012] Furthermore, after the hydrocarbon resin is allowed to flow, fill the interlayer gaps, and cure and bond, the process further includes: releasing the vacuum, and gradually reducing the temperature and pressure to relieve thermal stress on the circuit board. Gradient cooling can effectively reduce interlayer thermal stress caused by differences in the coefficients of thermal expansion of heterogeneous materials.

[0013] Further, the first temperature is 100°C to 130°C, and the first pressure is 80 to 120 PSI; the curing temperature is 210°C to 230°C, and the curing pressure is 350 to 450 PSI. This parameter range is an optimal window obtained by optimizing the material system based on a hydrocarbon resin TG of approximately 200°C and a buried pore layer resin TG of approximately 220°C.

[0014] A second aspect of this invention provides a printed circuit board manufactured using the aforementioned mixed-pressing method, comprising: at least one blind via layer, the blind via layer being composed of glass fiber-free hydrocarbon resin-coated copper foil; at least one buried via layer; the blind via layer and the buried via layer are alternately stacked and bonded together by high-temperature and high-pressure pressing. Due to the manufacturing method described above, the blind via layer of this printed circuit board has no glass fiber residue, the interlayer bonding is tight and bubble-free, and it exhibits excellent structural reliability.

[0015] Furthermore, the buried via layer is composed of a resin substrate with a glass transition temperature of not less than 200°C.

[0016] Furthermore, the printed circuit board is a high-density interconnect layer uplayer board with a density of 10 or higher.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This solution fundamentally solves the technical bottleneck of Q-cloth's inability to be laser-vaporized in blind via processing of M9-level high-speed printed circuit boards. It replaces the traditional Q-cloth-containing PP material with glass fiber-free hydrocarbon resin-coated copper foil. Hydrocarbon resin, an organic polymer, can be effectively decomposed and vaporized under high-energy laser light, eliminating the need to treat glass fiber residue. This solution bypasses the fundamental obstacle of pure silica composition in Q-cloth for laser processing, paving the way for a clear material technology route for the development of 224G high-speed printed circuit boards.

[0018] 2. By cleverly utilizing the interconnected micropores and rough surface structure of the RCC copper foil itself as an in-situ venting channel, combined with a vacuum low-temperature venting process, the gas within the stack is fully discharged before the resin flow window closes. Compared with the traditional solution that relies on the edges of PP glass fiber bundles for venting, this solution distributes the venting channels across the entire contact surface between the copper foil and the resin, resulting in a larger venting area, shorter path, and higher efficiency. This fundamentally solves the problems of bubbles and delamination caused by residual gas in the mixing and pressing of heterogeneous materials.

[0019] 3. By controlling the curing temperature to reach or exceed the glass transition temperature of the buried via layer resin, both resin systems are simultaneously in a flowable state within their optimal temperature window, achieving sufficient molecular-level interdiffusion and wetting at the interface. Curing pressure ensures tight contact between the two layers, eliminating micropores and improving interfacial bonding strength. High-temperature, high-pressure, and long-term heat treatment allows both resins to complete a full cross-linking and curing reaction, guaranteeing the overall structural strength of the circuit board.

[0020] 4. A gradient cooling method is used to release the thermal stress of the heterogeneous material mixed-pressure structure. Due to the inherent difference in the coefficients of thermal expansion between hydrocarbon resin and buried via layer resin, the temperature and pressure are released slowly during the cooling process, and the temperature gradient is reduced in stages. This allows the resin sufficient time to relax its stress, effectively avoiding thermal shock, interlayer separation, and board warping caused by sudden cooling, and improving the dimensional stability and reliability of the circuit board.

[0021] 5. This hybrid pressing method supports the fabrication of high-density interconnect (HDI) boards of order 10 and above. The reliable combination of multilayer blind via layers and buried via layers provides a technological basis for the manufacture of ultra-high-order HDI boards, meeting the dual requirements of high wiring density and inter-layer reliability for high-speed signal transmission of 224G and above. Attached Figure Description

[0022] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1 This is a schematic diagram of a mixed-pressure structure of M9 hydrocarbon RCC and carrier BT material.

[0024] Figure 2 This is a schematic diagram of a 20-layer circuit board.

[0025] The correspondence between the numbers and component names in the diagram is as follows: 100 bottom solder mask layer, 200 buried via layer area, 210 BT resin-based prepreg, 220 BT resin-based copper clad laminate, 300 blind via layer area, 310 fiberglass-free hydrocarbon resin layer, 320 copper foil with a rough surface structure of interconnected micropores. Detailed Implementation

[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. However, this should not be construed as limiting the scope of the invention to the following embodiments. All technical solutions implemented based on the above-described contents of this invention should fall within the protection scope of this invention. Hereinafter, fiberglass-free hydrocarbon resin-coated copper foil will be abbreviated as hydrocarbon RCC. Example 1

[0027] This embodiment uses materials produced by Shengyi Technology as an example to demonstrate the method of mixing and pressing M9 hydrocarbon RCC with carrier BT material. The following material models are only used as specific choices for the embodiment and do not constitute a limitation on the scope of protection of this invention.

[0028] Step S1: Material Preparation. The blind via layer material is Shengyi SIF09(R) type M9 hydrocarbon RCC copper foil, which is a glass fiber-free hydrocarbon resin-coated copper foil. The hydrocarbon resin layer is directly laminated to the copper foil, without any glass fiber reinforcement. The surface of the copper foil in contact with the hydrocarbon resin undergoes a special roughening treatment, resulting in a rough surface structure with interconnected micropores. This rough surface manifests as a microscopic undulating morphology on the copper foil side, where protrusions are embedded in the resin layer, and recesses form interconnected microchannels. The pore size of these interconnected micropores is typically in the submicron to several micrometer range, remaining open before the hydrocarbon RCC is subjected to heat pressing, forming a microscopic gas transport network extending from the interior of the stack to the edge. In this embodiment, the thickness of the SIF09(R) hydrocarbon resin layer is approximately 0.081 mm, and its glass transition temperature is approximately 200°C. The copper foil thickness is 1 / 3 oz, and the surface roughness Rz after roughening treatment is in the range of 3 to 8 μm. The aforementioned hydrocarbon resin is a low-dielectric-loss thermosetting resin system with a carbon-hydrogen backbone. In another alternative embodiment, the hydrocarbon resin may include modified hydrocarbon copolymers, such as hydrocarbon resins modified with polar groups, to further improve the adhesion to the copper foil. In yet another alternative embodiment, inorganic fillers such as silica powder may be added to the hydrocarbon resin system to reduce the coefficient of thermal expansion; the amount of filler added is controlled within the range of 5% to 30% of the resin volume. The roughness Rz of the interconnected micropore rough surface structure of the aforementioned copper foil is in the range of 3 to 8 μm. In another alternative embodiment, a copper foil with a higher roughness is used, with an Rz reaching 8 to 15 μm, further increasing the cross-sectional area and connectivity of the interconnected micropores and improving venting efficiency. In yet another alternative embodiment, a copper foil with a lower roughness is used, with an Rz in the range of 1.5 to 3 μm, suitable for hydrocarbon RCC products with a thinner resin layer thickness, such as less than 0.05 mm. Although the venting efficiency is slightly lower, sufficient venting can still be achieved by combining it with a longer low-temperature venting time. The buried via layer material is a Shengyi SI05NFQ type carrier BT resin-based copper clad laminate, with a glass transition temperature of approximately 220°C for BT resin. Alternatively, a BT resin-based prepreg of the same system, type 1067, can be used, with two sheets stacked together. In another alternative embodiment, the buried via layer can use other types of resin substrates with a glass transition temperature not lower than 200°C, such as high-TG modified epoxy resin, polyimide resin, cyanate ester resin, or a blend of BT and other resins. The selection principle is that the resin in the buried via layer should be able to soften and flow sufficiently at the pressing and curing temperature, and should be chemically compatible with hydrocarbon resins, without repulsion or delamination at high temperatures. In yet another alternative embodiment, the buried via layer can use a resin substrate with a glass transition temperature between 180°C and 200°C, in which case the curing temperature is adjusted accordingly to a temperature range slightly higher than this TG value.

[0029] Step S2: Stacking. (Refer to...) Figure 1 and Figure 2The layered structure shown is as follows. The blind via layer material and the buried via layer material are arranged in an alternating manner, that is, the blind via layer, the buried via layer, the blind via layer, and the buried via layer are stacked in sequence to form a multi-layer structure, which constitutes the stack of plates to be pressed. Figure 1 A representative mixed-pressure interface structure is shown: At the bottom is a bottom solder mask layer 100, above which is a BT resin-based prepreg 210 as part of the buried via layer; above 210 is a BT resin-based copper clad laminate 220; above 220 is a glass fiber-free hydrocarbon resin layer 310 as a blind via layer; and above 310 is a copper foil 320 with a rough surface structure featuring interconnected micropores. 210 and 220 together constitute the buried via layer region 200, and 310 and 320 together constitute the blind via layer region 300. It should be noted that... Figure 1 The layers shown are stacked alternately in a separate state before pressing. After pressing, the resin in 210 melts, flows and solidifies, forming a tight bond without gaps between 210 and 220, and between 220 and 310. Figure 1 The drawing method of directly bonding adjacent layers represents this finished product state, where the thick solid lines at the top and bottom edges of 220 represent its own copper foil layer. Figure 2 The diagram shows a complete 20-layer circuit board structure (for reference only). In actual products, multiple alternation cycles can be set as needed. For example, the number of layers can be as low as 4 (2 blind via layers and 2 buried via layers), suitable for simple HDI boards. In another alternative implementation, the number of layers can be as high as 30 or more, suitable for ultra-high density interconnect build-up boards with 10 or more layers. The choice of the number of layers depends on the product's signal layer and power layer requirements.

[0030] Step S3: Low-temperature, low-pressure vacuum exhaust. Under vacuum conditions, the stack of plates to be pressed is heated and pressurized at a first temperature and a first pressure. Stage 1: Within 2 minutes, the pressure is increased to 100 PSI and the temperature to 120°C. This temperature is maintained at 120°C and 100 PSI for 10 minutes, with the vacuum maintained throughout. The temperature at this stage is the first temperature of 120°C, and the pressure is the first pressure of 100 PSI. Under these temperature conditions, the hydrocarbon resin is in a solid state or only its surface is initially softened; its overall viscosity is extremely high, far from being flowable. The interconnected micropores and rough surface structure of the copper foil remain completely open at this stage, forming unobstructed microscopic exhaust channels. The vacuum environment establishes a pressure difference between the inside and outside of the stack, driving air, moisture, and residual low-molecular-weight volatiles in the resin to migrate outward through the microporous network of the copper foil and be extracted. The low-temperature condition prevents premature softening of the resin surface during rapid heating, which would close the exhaust channels and trap internal gases. In another alternative embodiment, the first temperature can be 100°C, suitable for cases where the softening point of the hydrocarbon resin is low, requiring a longer holding time of 10 to 12 minutes. In yet another alternative embodiment, the first temperature can be 130°C, suitable for cases where the softening point of the hydrocarbon resin is high, and the holding time can be correspondingly shortened to 5 to 7 minutes. The selection principle is: the first temperature should be lower than the temperature at which the hydrocarbon resin begins to soften significantly, so that the micropores of the copper foil remain open during the venting stage. In another alternative embodiment, the first pressure can be 80 PSI, used when interlayer contact is initially established, and with vacuum suction, the venting path is more unobstructed. In yet another alternative embodiment, the first pressure can be 120 PSI, used when the total thickness of the stacked boards is large and a slightly higher pressure is required to ensure basic interlayer adhesion. It should be noted that the first pressure should not be too high, otherwise it may prematurely close the micropores of the copper foil or cause the resin to be squeezed and flowed before venting is completed.

[0031] Step S4: Gradually increase temperature and pressure to allow the resin to flow and fill. While maintaining a vacuum, gradually increase the temperature and pressure. Stage 2: Maintain pressure at 100 PSI, and raise the temperature to 140°C within 10 minutes. Stage 3: Raise the pressure to 150 PSI within 10 minutes, and maintain the temperature at 140°C for 15 minutes. Stage 4: Maintain pressure at 150 PSI, and raise the temperature to 160°C within 10 minutes. Stage 5: Maintain pressure at 150 PSI, and maintain the temperature at 160°C for 10 minutes. Vacuum is maintained throughout. In this stage, the temperature gradually increases from 120°C to 160°C (the second temperature), and the pressure gradually increases from 100 PSI to 150 PSI (the second pressure). Within this temperature range, the hydrocarbon resin undergoes a softening and melting transition, its viscosity significantly decreases, and it begins to flow and fill the gaps in the circuit pattern. During the gradual heating and pressurization process, as the resin flow front advances, residual gas in the interlayer gaps is driven to the unclosed micropore channels and eventually extracted under vacuum. Maintaining a constant temperature of 140°C for 15 minutes in the third stage provides an optimal flow window for the hydrocarbon resin, allowing it to fully wet and fill the gaps at a lower viscosity, while the venting channels are not yet completely closed. The fifth stage, maintaining a constant temperature of 160°C, marks the beginning of the initial cross-linking reaction, i.e., gelation, of the hydrocarbon resin, and the venting process concludes here. The aforementioned gradual heating employs a multi-stage, stepped path of heating and holding at different temperatures. In another alternative embodiment, the gradual heating can be achieved through a continuous, slow heating method, for example, directly increasing the temperature from the first temperature to the second temperature (140°C to 160°C) at a constant rate of 0.5 to 1°C per minute. This eliminates the need for multiple constant temperature stages and is suitable for PCB stack structures with simple circuit patterns and low gap-filling difficulty. In another alternative embodiment, the gradual heating can be carried out using a variable rate heating method that is fast at first and then slow. For example, the temperature can be increased at a faster rate, such as 2°C per minute to 130°C in the lower temperature range, and then the rate can be changed to a slower rate, such as 0.5°C per minute to 160°C, after approaching the softening temperature of the hydrocarbon resin, so as to obtain a longer venting time in the resin flow window region.

[0032] Step S5: High-Temperature and High-Pressure Curing. While maintaining vacuum, raise the temperature to the curing temperature and apply curing pressure. Stage 6: Increase pressure to 280 PSI within 5 minutes, increase temperature to 185°C within 5 minutes, and hold for 15 minutes. Stage 7: Maintain pressure at 280 PSI, increase temperature to 220°C within 5 minutes, and hold for 25 minutes. Stage 8: Increase pressure to 400 PSI, maintain temperature at 220°C, and hold for 70 minutes. Vacuum is maintained throughout the process. Stage 7 reaches the curing temperature of 220°C, which is at or above the glass transition temperature (GLT) of the BT resin for the buried via layer. Above its TG temperature, the molecular chain segments of the BT resin gain sufficient energy to undergo large-scale motion, and the resin enters a highly elastic state, exhibiting good fluidity. The hydrocarbon resin is also in a fully fluid state at this time. The two resins interwet and diffuse at the interface, forming an interfacial bonding layer. The eighth stage, with a pressure increased to 400 PSI (curing pressure), uses high pressure to compact the two resin layers, eliminating micro-voids and creating a denser interfacial bond. Maintaining the pressure at 220°C and 400 PSI for 70 minutes ensures the BT resin completes its full cross-linking and curing reaction, while the hydrocarbon resin cures simultaneously, forming a stable three-dimensional cross-linked network structure. In another alternative embodiment, the curing temperature can be 210°C, slightly lower than the buried via layer's TG value of 220°C. In this case, the curing time needs to be extended, such as 90 to 120 minutes, to allow the BT resin to fully cure through prolonged heat treatment at a temperature slightly below the TG value. In yet another alternative embodiment, the curing temperature can be 230°C, slightly higher than the buried via layer's TG value by 10°C. The holding time can be shortened to 50 to 60 minutes, but care must be taken not to exceed the thermal decomposition temperature of the hydrocarbon resin. In another alternative embodiment, the curing pressure can be 350 PSI, suitable for situations where the buried via layer resin has good fluidity. In yet another alternative embodiment, the curing pressure can be 450 PSI, suitable for situations with thicker copper layers requiring higher pressure compaction.

[0033] Step S6: Gradual cooling to release thermal stress. Release the vacuum and reduce the temperature and pressure in stages. Stage 9: Close the vacuum, reduce the pressure to 280 PSI within 10 minutes, and the temperature to 180°C within 10 minutes, hold for 30 minutes. Stage 10: Reduce the pressure to 150 PSI within 10 minutes, and the temperature to 130°C within 10 minutes, hold for 20 minutes. Stage 11: Maintain the pressure at 100 PSI and the temperature at 100°C for 15 minutes. Stage 12: Maintain the pressure at 100 PSI and the temperature at 80°C for 15 minutes. Stage 13: Maintain the pressure at 100 PSI and the temperature at 80°C for 30 minutes. In this stage, the temperature is gradually reduced from 220°C to 80°C, and the pressure is gradually reduced from 400 PSI to 100 PSI, with a total cooling time of approximately 130 minutes. The heterogeneous materials, namely hydrocarbon resin and BT resin, have different coefficients of thermal expansion. If rapid cooling occurs after curing, significant thermal stress will be generated at the interface. Gradual cooling keeps the temperature difference within a reasonable range at each stage, allowing the resin sufficient time to relax stress and avoiding thermal shock and delamination caused by sudden cooling. The prolonged low-temperature holding in stages 11 to 13 ensures a uniform temperature drop across all areas of the board, preventing localized temperature differences that could lead to copper surface deformation or board warping. This completes the mixed-press manufacturing of the circuit board. Example 2

[0034] This embodiment is a modification of Embodiment 1, mainly demonstrating another way to realize the overarching concept of gradually increasing the curing temperature and curing pressure. Unlike the 13-segment detailed program used in Embodiment 1, this embodiment uses a simplified 5-segment pressing program, as detailed below.

[0035] Step S1: Low-temperature, low-pressure vacuum exhaust stage. The temperature rises to 120°C, the pressure rises to 100 PSI, and the temperature and pressure are maintained for 10 minutes before vacuuming begins. The exhaust principle is the same as in Example 1.

[0036] Step S2: Continuous Slow Heating and Pressurization Stage. Under vacuum conditions, the temperature is continuously increased from 120°C to 220°C (the curing temperature) and the pressure is continuously increased from 100 PSI to 400 PSI (the curing pressure) at a heating rate of approximately 1°C per minute and a pressurization rate of approximately 2 PSI per minute, lasting approximately 100 minutes. This stage employs continuous linear heating and pressurization, without intermediate isothermal and pressure control sections. In the early heating phase (120°C to 160°C), the hydrocarbon resin gradually softens and flows to fill the interlayer gaps. In the middle heating phase (160°C to 200°C), the hydrocarbon resin enters the gelation stage. In the later heating phase (200°C to 220°C), the BT resin also reaches a softened and flowing state, wetting itself with the hydrocarbon resin at the interface. This continuous linear heating method also falls within the protection range of gradually increasing the temperature and pressure to the curing temperature and pressure.

[0037] Step S3: High-temperature and high-pressure curing stage. Temperature 220℃, pressure 400 PSI, heat and pressure held for 60 minutes, vacuum maintained. Same as the high-temperature curing principle in Example 1.

[0038] Step S4: Slow cooling phase. With the vacuum closed, the temperature is reduced from 220°C to 100°C at a cooling rate of approximately 1°C per minute and a pressure reduction rate of approximately 5 PSI per minute, with the pressure simultaneously reduced to 100 PSI, for a total of approximately 120 minutes.

[0039] Step S5: Low-temperature stabilization stage. Maintain the temperature at 100℃ and the pressure at 100 PSI for 20 minutes, then allow it to cool naturally to room temperature. This completes the mixed-pressure manufacturing of the circuit board.

[0040] This embodiment demonstrates a different approach to achieving gradual heating and segmented cooling compared to Embodiment 1. Embodiment 1 uses a multi-stage, stepped heating method, while this embodiment uses a continuous, linear heating method. Both fall within the protection range of gradually increasing temperature and pressure to the curing temperature and pressure. Embodiment 1 uses a multi-stage, gradient cooling method, while this embodiment uses a single-stage, linear, slow cooling method combined with low-temperature stabilization. Both achieve the goal of releasing thermal stress.

[0041] The working principle of this invention can be summarized as a structural-temporal synergistic venting and gradient curing mechanism. At the structural level, the copper foil of the fiberglass-free hydrocarbon resin-coated copper foil has a rough surface structure with interconnected micropores. This structure, originally used in hydrocarbon RCC materials to increase the contact area between the copper foil and the resin to improve adhesion, also objectively forms a microscopic gas transport network extending from the interior of the stack to the edges. This invention identifies and utilizes this structural feature as an in-situ venting channel, eliminating the need for additional venting grooves or channels in the stack and avoiding reliance on the limited venting paths at the edges of the PP fiberglass bundles. Instead, it utilizes the microporous network of the copper foil across the entire surface to achieve large-area uniform venting. At the temporal level, the pressing process strictly follows the sequence of venting, flow, curing, and finally slow cooling. During the venting stage, temperature and pressure are controlled within the low-temperature, low-pressure range where the resin has not softened and flowed, ensuring that the microporous venting channels remain open, and the vacuum environment drives the gas to migrate outwards. During the flow stage, the temperature gradually increases, causing the resin viscosity to gradually decrease, and the pressure gradually increases, pushing the resin to fill the gaps. Residual gas is further driven out and discharged under the pressure of the flow front. During the curing stage, the temperature reaches or exceeds the TG value of the buried pore layer resin, causing both resins to soften sufficiently and undergo molecular-level diffusion at the interface. High-pressure compaction eliminates micropores. During the cooling stage, gradient cooling gradually releases thermal stress. The effectiveness of this structural-temporal synergistic mechanism is based on the following causal chain: the open state of the copper foil micropores depends on the temperature-viscosity state of the resin; the temperature-viscosity state of the resin is controlled by the temperature curve of the pressing program; the vacuum degassing time window is determined by the micropore closing time; and the micropore closing time is influenced by the heating curve. This multi-parameter synergistic matching relationship has not been recognized or disclosed in the prior art.

[0042] Comparative Example: If, after the low-temperature, low-pressure vacuum venting in step S3, the temperature is rapidly increased from 120°C to 220°C via a jump (i.e., a non-gradual increase), the following problems will occur: the surface layer of the hydrocarbon resin softens and flows instantly under the high-temperature impact; the micropores of the copper foil are filled and sealed by the molten resin within seconds; and residual gas in the deep gaps is trapped inside the resin before it can be expelled. Simultaneously, due to the temperature jump, there is a significant temperature difference between the inner and outer layers of the laminate; the outer resin solidifies first while the inner resin has not yet fully flowed, resulting in uneven interlayer bonding. Furthermore, the rapid heating causes the resin flow front to advance irregularly, easily forming trapped pores in the filling gaps. Therefore, a gradual increase rather than a jump is the key process feature for achieving bubble-free mixing and pressing in this scheme.

[0043] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for bonding blind via layer material and buried via layer material into a printed circuit board, characterized in that, Includes the following steps: A blind via layer material is provided, wherein the blind via layer material is a glass fiber-free hydrocarbon resin-coated copper foil, and the copper foil has a rough surface structure with interconnected micropores. The blind hole layer material and the buried hole layer material are alternately stacked to form a stack of plates to be pressed. Under vacuum conditions, the stack of plates to be pressed is heated and pressurized at a first temperature and a first pressure to expel the gas from the interconnected micropores of the copper foil; While maintaining a vacuum, the temperature and pressure are gradually increased to the curing temperature and curing pressure, causing the hydrocarbon resin to flow, fill the interlayer gaps, and cure and bond.

2. The method for mixing and pressing printed circuit boards according to claim 1, characterized in that, The buried hole layer material is a resin substrate with a glass transition temperature of not less than 200°C.

3. The mixed-pressing method for printed circuit boards according to claim 2, characterized in that, The buried via layer material is BT resin-based copper clad laminate or BT resin-based prepreg.

4. The method for mixing and pressing printed circuit boards according to claim 1, characterized in that, The step of gradually increasing the temperature and pressure to the curing temperature and curing pressure includes: first gradually increasing the temperature and pressure from the first temperature and first pressure to the second temperature and second pressure, and maintaining the second temperature and second pressure for a predetermined time to allow the hydrocarbon resin to fully flow and fill the interlayer gaps, and then increasing it to the curing temperature and curing pressure.

5. The method for mixing and pressing printed circuit boards according to claim 2, characterized in that, The curing temperature reaches or exceeds the glass transition temperature of the buried hole layer material.

6. The method for mixing and laminating printed circuit boards according to claim 1, characterized in that, After the hydrocarbon resin is allowed to flow and fill the interlayer gaps and then cured and bonded, the process further includes: releasing the vacuum and reducing the temperature and pressure in stages to relieve the thermal stress on the circuit board.

7. The method for mixing and laminating printed circuit boards according to claim 1, characterized in that, The first temperature is 100°C to 130°C, and the first pressure is 80 to 120 PSI; the curing temperature is 210°C to 230°C, and the curing pressure is 350 to 450 PSI.

8. A printed circuit board, manufactured using the mixed-pressing method as described in any one of claims 1 to 7, characterized in that, include: At least one blind via layer, the blind via layer being composed of glass fiber-free hydrocarbon resin-coated copper foil; At least one buried borehole layer; The blind hole layer and the buried hole layer are alternately stacked and bonded together by high temperature and high pressure.

9. The printed circuit board according to claim 8, characterized in that, The buried hole layer is composed of a resin substrate with a glass transition temperature of not less than 200°C.

10. The printed circuit board according to claim 8, characterized in that, The printed circuit board is a high-density interconnect layered board with a density of 10 or higher.